Motivation, Perceptions, and Preferences of Tourists Visiting National Parks on the Java and Sulawesi Islands - Bukit, Windi Liani; Kusrini, Mirza D.; Rachmawati, Eva; Dewi, Tungga; Adinda, Esther; Hapsari Ayuningtyas, Aniis (Media Konservasi, 2025)
Understanding tourist motivation, perception, and preferences is critical for designing effective tourism strategies in national parks. This study examines the relationship between ecological factors and the motivations, perceptions, and preferences of domestic tourists visiting national parks in Java and Sulawesi, Indonesia. Data were collected from 358 respondents via an online survey over four months and analyzed using chi-square and General Linear Model tests to assess socio-demographic differences. The main motivation for visiting national parks in Java was "attractive natural panoramas", while in Sulawesi, it was the "diversity of fauna". Tourists in Java exhibited stronger cognitive perceptions due to informative signage, whereas Sulawesi visitors appreciated the "natural appearance of facilities". Affective perceptions were consistent across both islands, driven by enjoyment, while conative perceptions were linked to intentions to revisit for wildlife observation. Activity preferences varied, with Java tourists favoring natural panoramas and Sulawesi visitors prioritizing wildlife observation. The length of visit was the only socio-demographic variable significantly related to motivations, perceptions, and preferences. These findings highlight the varying ecological priorities of tourists in Java and Sulawesi, with implications for targeted management and conservation strategies in national parks.